Exploring the Influence of Family Environment on Entrepreneurial Interests Among Agribusiness Management Students - Waridad Umais Al Ayyubi; Firmansyah, Akbar Maulana; Atmojo, Titin Andriani; Musi, Ngani Alwirya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines how the family environment affects the entrepreneurial interest of students in the Agribusiness Management program at Campus 5 Ngawi. The research is motivated by the high unemployment rate and low education levels in Ngawi. Using a quantitative approach and a survey of 29 students, the study identifies the family environment as the independent variable and entrepreneurial interest as the dependent variable. The research instrument was tested for validity and reliability with SPSS, and data were analyzed using simple linear regression. The findings show that the family environment significantly influences entrepreneurial interest, contributing 66%. Key factors include parenting style, family relationships, home atmosphere, economic conditions, and cultural background. The study emphasizes the critical role of the family in fostering an entrepreneurial mindset in students from an early age and recommends parental involvement in creating a supportive environment for their children's entrepreneurial development.